Solid state chemistry : an introduction - Smart, Lesley; Moore, Elaine (Elaine A.) (Boca Raton : CRC Press, 2012)
'The fourth edition of this volume has been comprehensively revised and updated. Building a foundation with a thorough description of crystalline structures, the book presents a wide range of the synthetic and physical techniques used to prepare and characterize solids. The text discusses bonding, superconductivity, and electrochemical, magnetic, optical, and conductive properties. The authors have updated sections to cover STEM, ionic conductivity, nanotubes and related structures such as graphene, metal-organic frameworks, and FeAs superconductors. They also include additional new chapters on biological systems in synthesis, solid state modeling, metamaterials.'--
Includes bibliographical references and index.
Keywords: Solid state chemistry